What to Do About Missed Doses? A Retrospective Study of Olanzapine in the Elderly - Xiao T; Wang Z; Li G; Huang S; Zhu X; Liu S; Li X; Hu J; Shang D; Wen Y (Dove Medical Press, 2021)
Tao Xiao,1,2,* Zhanzhang Wang,1,2,* Guanlie Li,3 Shanqing Huang,1,2 Xiuqing Zhu,1,2 Shujing Liu,1,2 Xiaolin Li,1,2 Jinqing Hu,1,2 Dewei Shang,1,2 Yuguan Wen1,2 1Department of Pharmacy, The Affiliated Brain Hospital of Guangzhou Medical University, Guangzhou, 510370, People's Republic of China; 2Guangdong Engineering Technology Research Center for Translational Medicine of Mental Disorders, Guangzhou, 510370, People's Republic of China; 3Key Laboratory of Molecular Target & Clinical Pharmacology, School of Pharmaceutical Sciences, Guangzhou Medical University, Guangzhou, 511436, People's Republic of China*These authors contributed equally to this workCorrespondence: Yuguan Wen; Dewei ShangDepartment of Pharmacy, The Affiliated Brain Hospital of Guangzhou Medical University, 36 Mingxin Road, Guangzhou, 510370, People's Republic of ChinaTel +86-020-81268389Fax +86-020-81891391Email wenyuguande@163.com; shang_dewei@163.comBackground: Schizophrenia is characterized by a high disease burden. Olanzapine is a common drug used in antipsychotic medication. Little is known about the population pharmacokinetics of olanzapine in elderly patients. Missed doses are a common and unavoidable issue during the treatment of psychiatric diseases, especially in elderly patients. This study aimed to identify what an elderly person should do if doses are inadvertently missed.Methods: Data were collected from 140 elderly psychiatric patients (aged ≥ 65 years) who received olanzapine therapy. Olanzapine concentrations were determined by high pressure liquid chromatographic tandem mass spectrometry (HPLC-MS/MS) and a population-based approach was used to quantify the characteristics of elderly patients. A non-linear mixed-effects model was used for data analysis. Simulations based on the final model were applied to predict situations involving a single missed dose or three consecutive missed doses under several remedial regimens.Results: A total of 474 samples from 140 elderly patients were included in the therapeutic drug monitoring (TDM) data analysis. A one-compartment model, with no significant covariates, was developed to describe the population pharmacokinetics of olanzapine in elderly patients. The population predicted systematic clearance (CL/F) and volumes of distribution (V/F) were 18 L/h and 785 L, respectively. The simulation demonstrated that in a missed dose situation, elderly patients should take the regular dose immediately; the refill dose used at the second remedial time point depends on the length of the time delay.Conclusion: Here, we used a simulation to provide a remedial regimen for missed doses of olanzapine in the elderly population. Our simulation can provide valuable suggestions for individualized therapy in elderly patients.Keywords: olanzapine, elderly patients, missed doses, simulation, remedial regimen